Viticultural Traditions and Local Memory - Popelková, Katarína (Lidé města, 2008)
This paper discusses the process of construction of representation of an urban space as a socially determined phenomenon under the conditions of the postcommunist transformation of Slovakia. The subject matter of the analysis is the occurrence of facts from the viticultural past – a common feature of two neighboring towns – in their current public discourse. On the basis of data gather through archival-document study and ethnological field research, the paper analyzes collective motivations in the process of construction of collective memory and their linkages to concrete conditions of revitalization of private entrepreneurship after 1989.